Simulation-based learning in postgraduate critical care and anaesthesia nursing: an interview study from postgraduate nurses’ perspectives - Carina Sjöberg; Pether Jildenstål; Mona Ringdal; Torben Nordahl Amorøe; Viktoria Sjöstedt; Carl-Johan Cederwall (BMC Nursing)
Abstract Background Simulation-based learning is used to educate students in anaesthetics and critical care. At the postgraduate level, the aim is to foster an understanding of the connection between theory and practice and prepare nurses for the clinical environment. In this context, we created a new wherein we integrated simulation-based learning with clinical learning activities e.g. before start of clinical practice, during and after end of clinical practice. The postgraduate nurses were educated and instructed by university teachers from the postgraduate program and clinical active tutors, critical care nurses and registered nurse anaesthetists from the simulation center. This study aimed to explore the experiences of postgraduate nurses with simulation-based learning and its impact on their overall learning outcomes. Method This is a descriptive qualitative interview study with a purposeful sample of postgraduate nurses with experience with simulation-based learning during clinical practice. The data were analysed using inductive and thematic analysis. Results We identified two themes ‘pros of simulation-based learning’ and ‘cons of simulation- based learning’ describing opportunities and obstacles related to the postgraduate nurses’ experience of simulation-based learning. ‘Pros of simulation-based learning’ included the subthemes ‘learning through scenarios facilitates preparedness for clinical practice,’ ‘learning via reflection gives you time to think over your actions’ and ‘Learning from tutors is valuable and highly regarded ‘Cons of simulation based learning’ included the subthemes ‘it is difficult to accept the simulation situation and environment, ‘the design of the scenarios and technical conditions constitutes a barrier’ and ‘Unfamiliar groups interfere with learning. Conclusion This study shows that simulation-based learning activities promoted postgraduate nurses learning especially later in the education. Competence required for critical care nurses and registered nurse anesthetists is situational and competence specific, theoretical background and clinical experience are therefore required to promote progression in learning.